Mean Atd Angle among Type 2 Diabetes Mellitus Patients Visiting a Tertiary Care Centre: A Descriptive Cross-sectional Study - Sheprala Shrestha; Dil Islam Mansur; Rajendra Tamrakar; Pragya Shrestha; Sunima Maskey (Journal of Nepal Medical Association, 2023)
Introduction: An atd angle is one of the dermatoglyphic patterns which is an indication of the degree of distal displacement of the axial triradius on the palm. This is one of the markers of diabetes mellitus that is used as a screening tool in order to reduce the risk of onset and initiate early treatment. The aim of this study is to find the mean atd angle among type 2 diabetes mellitus patients visiting a tertiary care centre.